THE EFFECT OF SALES PROMOTION AND PRICE DISCOUNT ON IMPULSE BUYING FOR HIJAB CONSUMERS AT AL-HUDA SRAGI ISLAMIC BOARDING SCHOOL BANYUWANGI - Nurul Inayah; Abdul Kholiq Syafaat; Ratih Hatma Maghfiroh (International Conference on Humanity Education and Society (ICHES), 2023)
The purpose of this study is: To determine and analyze the influence of sales promotion and price discount variables on the impulse buying variable on hijab consumers at Al-Huda Islamic Boarding School in Sragi Banyuwangi Village. This study uses an explanatory research type with a quantitative approach to the associative model. The results of this study indicate that there is a significant influence between sales promotion and price discount on impulse buying with an effect of 74% and 26% are affected by other factors with a population of 150 and a Sampel picker 20% (30) respondents. The conclusion of this study is there is a significant influx of impulse buying which is influenced by the existence of sales promotion factors and price discount